TINGKAT LIVABILITAS RUANG TERBUKA PUBLIK PADA PANTAI NYANG NYANG BERDASARKAN PERSEPSI WISATAWAN MANCANEGARA - M.D. Hermawan; S.R. Girsang; K.B.P.K. Vedanta; N. Siaindo; T.A. Prajnawrdhi (Buletin Udayana Mengabdi, 2024)
The beach is one of the most popular public open spaces, especially on the island of Bali, especially in Pecatu Village. The high number of beach visitors, especially foreign tourists, demands various needs and supporting facilities that need to be met to ensure visitor comfort and optimize the potential of public open spaces to accommodate activities, as a livability factor. The purpose of this survey and paper is to interpret the quality of a beach based on the livability factor and the potential of public area facilities that can be developed. Good beach open space livability will create a comfortable and pleasant feeling for visitors, thus inviting tourists to do activities in it which directly impacts the economic progress of the Pecatu Village community. This paper was made based on the results of observations on public open spaces at Nyang Nyang Beach from September 2022 to January 2023 which were processed using a quantitative analysis method. The results of the quantitative analysis of the questionnaire prove that the level of livability for public open space in Nyang Nyang Beach is still relatively low, therefore it is necessary to provide facilities and infrastructure in the area. Keywords: livability, Nyang Nyang Beach, public open space, facilities, foreign tourists